Using Drosophila to decipher how mutations associated with human branchio-oto-renal syndrome and optical defects compromise the protein tyrosine phosphatase and transcriptional functions of eyes absent. - Mutsuddi, M.; Chaffee, B.; Cassidy, J.; Silver, S.J.; Tootle, T.L.; Rebay, I. (Genetics, 2005)
Eyes absent (EYA) proteins are defined by a conserved C-terminal EYA domain (ED) that both contributes to its function as a transcriptional coactivator by mediating protein-protein interactions and possesses intrinsic protein tyrosine phosphatase activity. Mutations in human EYA1 result in an autosomal dominant disorder called branchio-oto-renal (BOR) syndrome as well as congenital cataracts and ocular defects (OD). Both BOR- and OD-associated missense mutations alter residues in the conserved ED as do three missense mutations identified from Drosophila eya alleles. To investigate the molecular mechanisms whereby these mutations disrupt EYA function, we tested their activity in a series of assays that measured in vivo function, phosphatase activity, transcriptional capability, and protein-protein interactions. We find that the OD-associated mutations retain significant in vivo activity whereas those derived from BOR patients show a striking decrease or loss of in vivo functionality. Protein-protein interactions, either with its partner transcription factor Sine oculis or with EYA itself, were not significantly compromised. Finally, the results of the biochemical assays suggest that both loss of protein tyrosine phosphatase activity and reduced transcriptional capability contribute to the impaired EYA function associated with BOR/OD syndrome, thus shedding new light into the molecular mechanisms underlying this disease.